Risk factors associated with non-alcoholic fatty liver disease in subjects from primary care units. A case-control study - Bernad Jesús; Canut Santiago; Birules Marti; Tibau Albert; Sanchez Carmen; Muñoz Laura; Casas José; Alumà Alba; Miranda Dolores; Pera Guillem; Torán Pere; Auladell Ma Antonia; et al. (BMC Gastroenterology, 2008)
Abstract Background Non alcoholic fatty liver disease (NAFL) consists in the accumulation of fat vacuoles in the cytoplasm of hepatocytes. Many etiologic factors are associated with NAFL, such as, the metabolic syndrome factors, medications, bariatric surgery, nutritional disorders. However, very little information is available on the clinical relevance of this disorder as a health problem in the general population. Methods and design The aim of the study is establish the risk factors most frequently associated with NAFL in a general adult population assigned to the primary care units and to investigate the relationship between each component of the metabolic syndrome and the risk of having a NAFL. A population based case-control, observational and multicenter study will be carried out in 18 primary care units from the "Area de Gestión del Barcelonés Nord y Maresme" (Barcelona) attending a population of 360,000 inhabitants and will include 326 cases and 370 controls. Cases are defined as all subjects fulfilling the inclusion criteria and with evidence of fatty liver in an abdominal ultrasonography performed for any reason. One control will be randomly selected for each case from the population, matched for age, gender and primary care center. Controls with fatty liver or other liver diseases will be excluded. All cases and controls will be asked about previous hepatic diseases, consumption of alcohol, smoking and drugs, and a physical examination, biochemical analyses including liver function tests, the different components of the metabolic syndrome and the HAIR score will also be performed. Paired controls will also undergo an abdominal ultrasonography. Discussion This study will attempt to determine the factors most frequently associated with the presence of NAFL investigate the relationship between the metabolic syndrome and the risk of fatty liver and study the influence of the different primary care professionals in avoiding the evolution of the disease.